Reflecting on our past, projecting into our future : Cave Hill @ 50 - 1963 - 2013 (UWI, Cave Hill Campus BridgetownBB, 2013)
Presents issue of CHILL magazine, celebrating the 50th anniversary of the Cave Hill Campus of the University of the West Indies.
Chill News, issue 14, 2013